Relativistic quantum field theory. - Strickland, M. T. (Michael Thomas), 1969- (IOP (Series). Release 6., 2019)
Volume 1 of this three-part series introduces the fundamental concepts of quantum field theory using the formalism of canonical quantization. This volume is intended for use as a text for an introductory quantum field theory course that can include both particle and condensed matter physics students. Dr. Strickland starts with a brief review of classical field theory and uses this as a jumping off point for the quantization of classical field, thereby promoting them to proper quantum fields. He then presents the formalism for real and complex scalar field theories, fermion field quantization, gauge field quantization, toy models of the nuclear interaction, and finally the full Lagrangian for QED and its renormalization. Part of IOP Series in Nuclear Medicine.